Validating the Efficacy of Yogic Practices on Pre Menstrual Syndrome in Young Adults. A Randomized Controlled Trial - Yadav, Amshuman R; K, Archana; KV, Swathi; HM, Prajwal; CN, Shravya; S, Swathi (Indian Journal of Integrative Medicine, 2024)
Background: Yoga has been used as a remedial treatment for ailments of Premenstrual Syndrome (PMS). The combined practices of yoga can be used as a systematic measure to overcome PMS to have a harmonious living. Aims & Objectives: The objective of this study was to validate the efficacy of yoga practices for PMS and to evaluate the effect of yogic practices for PMS on PSST-A. Materials and Methods: A total of 60 Premenstrual syndrome subjects aged 16-23 years were screened and after filling inclusion criteria as well as diagnostic criteria 39 subjects were recruited to the study. Pre assessments were made before the treatment. Expert validated yoga practices was given for the duration of 45 minutes each for 15 days. Post assessments was taken after the successive menstrual cycle of the intervention. All the details of the study were explained and consent was obtained from the subjects. Result: From PSST-A recordings, significant differences were detected in premenstrual symptoms. Subjects reported that there is a greater improvement in their sleep quality and daily living by reducing symptoms intensity and duration for combined yogic practices. Post analysis indicated PSST-A was improved from baseline (p ˂0.05), with reduction in the symptoms for the combined effect of yogic practices. Conclusion: This Yoga module is effective for the treatment of PMS. Significant differences has been found before and after the treatment. Hence combined practices of yoga plays a significant role in reducing the symptoms of PMS.